Physiotherapy Management in Post-Stroke Hemorrhage : A Case Report - Sutejo, Mianti Nurrizky; Ragil Aidil Fitriasari Addini; Linda Pramusinta (STIKES Telogorejo Semarang, 2023)
Post-stroke hemorrhage refers to bleeding that occurs in or around the brain following a stroke, particularly after a hemorrhagic stroke. This condition can lead to further brain damage and complications, necessitating immediate medical attention and intervention. Treatment of post-stroke hemmorrage can be given the intervention of the neuroplasticity and motor learning, and Bobath concept. Neuroplasticity is the brain's ability to reorganize itself by forming new neural connections, which is crucial for recovery after a stroke. The Bobath concept, or neurodevelopmental treatment, focuses on facilitating motor learning and functional movement in stroke patients, promoting recovery through tailored rehabilitation strategies. Purpose: The objectives of implementing interventions focused on neuroplasticity, motor learning, and the Bobath concept for patients post-stroke hemorrhage include enhancing neural recovery, improving motor function, promoting functional independence, and optimizing motor learning. Methods: a study using the case report method in a 50-year-old male patient diagnosed with left BPPV 6 months ago. The patient complains of a headache accompanied by a feeling of spinning and lightheadedness as well as muscle stiffness in the neck. Examination of the dix Hallpike maneuver in the patient was positive. Patients were given physiotherapy interventions in the form of Epley maneuvers and stretching exercises. Results: decreased dizziness and spinning sensation at the fifth meeting and stiffness of the neck muscles which were evaluated using the Numeric Rating Scale (NRS) and a 50% reduction at the third meeting which was evaluated using the Dizziness Handicap Inventory (DHI). Conclusion: there is effectiveness in reducing the sensation of spinning, neck muscle stiffness, and increasing functional ability in BPPV.